Answer to Question #253739 in Calculus for Shambo
2021-10-19T19:13:11-04:00
Use the fact that lim
tà ¢ 0
e
t à ¢ 1
t
= 1 to show from first principle that
d
dx(2e
2x à ¢ e
à ¢ x + 5x) = 4e
2x + e
à ¢ x + 5.
[
1
2021-10-20T12:52:59-0400
"f'(x)=\\lim\\limits_{h\\to0}\\dfrac{f(x+h)-f(x)}{h}"
"=\\lim\\limits_{h\\to0}\\dfrac{2e^{2(x+h)}+e^{x+h}+5(x+h)-2e^{2x}-e^x-5x}{h}="
"=\\lim\\limits_{h\\to0}\\dfrac{2e^{2x}(e^{2h}-1)}{h}+\\lim\\limits_{h\\to0}\\dfrac{e^{x}(e^{h}-1)}{h}+\\lim\\limits_{h\\to0}\\dfrac{5h}{h}"
"=4e^{2x}\\lim\\limits_{h\\to0}\\dfrac{e^{2h}-1}{2h}+e^x\\lim\\limits_{h\\to0}\\dfrac{e^h-1}{h}+5\\lim\\limits_{h\\to0}\\dfrac{h}{h}"
"=4e^{2x}(1)+e^x(1)+5(1)"
"=4e^{2x}+e^x+5"
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS !
Comments
Leave a comment